The technology of testing computer software using digital logarithmic arithmetic - Гамаюн, В. П.; Яременко, К. П.; Плотиков, Д. Б.; Панасенко, Е. О. (Problems of Informatization and Control, 2005)
It is offered to apply digital logarithmic computer arithmetic to testing software. Compatibility with binary arithmetic, an opportunity to use the known languages of a high level provides the analysis of quality of tasks realization in the computer environment at a new level